Enhancing employee wellbeing by ethical leadership in the construction industry: The role of perceived organizational support - Cheng, Jiajia; Zhang, Lianying; Lin, Yuan; Guo, Haiyan; Zhang, Shaoping (Frontiers in Public Health, 2022)
Employee well-being is a crucial determinant in overall organizational performance. However, in the construction industry, it is damaged by hazardous and stressful work environment. This study aims to explore how ethical leadership influences and thus could enhance employee well-being through perceived organizational support (POS). We proposed several hypotheses and developed the research framework accordingly. To test the hypotheses, an elaborately designed survey was used to collect quantitative data from 194 employees in the construction companies in China. Our results show that ethical leadership is positively related to the employee well-being. This study further reveals a remarkable indirect effect of ethical leadership on employee well-being via the mediating POS. Consequently, our findings suggest that, to enhance employee well-being, ethical leaders can develop a relaxing ethical environment and provide sufficient organizational support to the employees.